2015
DOI: 10.1002/chem.201502685
|View full text |Cite
|
Sign up to set email alerts
|

First N‐Heterocyclic Carbenes Relying on the Triazolone Structural Motif: Syntheses, Modifications and Reactivity

Abstract: 4-Phenylsemicarbazide and 1,5-diphenylcarbazide are suitable starting materials for the syntheses of N-heterocyclic carbene (NHC) compounds with new backbone structures. In the first case, cyclisation and subsequent methylation leads to a cationic precursor whose deprotonation affords the triazolon-ylidene 2, which was converted to the corresponding sulfur and selenium adducts and a range of metal complexes. In contrast, cyclisation of diphenylcarbazide affords a neutral betain-type NHC-precursor 7, which is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…This has led to a large compilation of TEP data for hundreds of NHC ligands, all using the same TEP scale. TEP values for NHCs generally stretch from 2030 cm –1 for electron rich NHCs to 2060 cm –1 for electron poor NHCs. This seems to be a small range of TEP values considering the large variety and complexity of NHC compounds as given by the following representative list: (i) NHCs with extended polyaromatic substituents; (ii) planar chiral imidazopyridinium based NHCs, which can function as Lewis acids and ligands for transition metal complexes; (iii) spiro-fused six-membered NHCs; (iv) polycyclic NHCs featuring a fused dibenz­[ a , c ]­phenazine moiety; (v) nanosized Janus bis-NHC ligands based on a quinoxalinophenanthrophenazine core; (vi) NHCs with O-functionalized triazole backbones; and (vii) cyclic alkyl aminocarbenes as strongly donating ligands at the lower end of the NHC-TEP scale …”
Section: Introductionmentioning
confidence: 99%
“…This has led to a large compilation of TEP data for hundreds of NHC ligands, all using the same TEP scale. TEP values for NHCs generally stretch from 2030 cm –1 for electron rich NHCs to 2060 cm –1 for electron poor NHCs. This seems to be a small range of TEP values considering the large variety and complexity of NHC compounds as given by the following representative list: (i) NHCs with extended polyaromatic substituents; (ii) planar chiral imidazopyridinium based NHCs, which can function as Lewis acids and ligands for transition metal complexes; (iii) spiro-fused six-membered NHCs; (iv) polycyclic NHCs featuring a fused dibenz­[ a , c ]­phenazine moiety; (v) nanosized Janus bis-NHC ligands based on a quinoxalinophenanthrophenazine core; (vi) NHCs with O-functionalized triazole backbones; and (vii) cyclic alkyl aminocarbenes as strongly donating ligands at the lower end of the NHC-TEP scale …”
Section: Introductionmentioning
confidence: 99%
“…The 77 Se NMR spectrum of bis-selenourea 7 shows a resonance at 115 ppm for the 2 equivalent selenium atoms, which is a relatively high chemical shift compared to that of standard imidazol- or triazolylidenes . A triazolonylidene, in which one Se atom in structure 7 is replaced by oxygen, showed a resonance at 137 ppm, reflecting its higher π-acidity due to the more electronegative oxygen . Note, however, that strongly π-acidic carbenes like CAACs , and amidocarbenes , feature 77 Se resonances up to ca.…”
Section: Resultsmentioning
confidence: 99%
“…6 pm longer than that in the related COD complex 12 (OTf). All bond lengths and angles fall in the range typically observed for (CO) 2 IrCl complexes with various NHC ligands. ,,, The Ir–CO bond trans to the NHC is longer (189.1(6) pm) than that in cis orientation (185.8(7) pm) due to the superior donor character of the chloride compared to the cationic carbene, thus promoting the π-backbonding to the CO trans to the chloride.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitron belongs to the class of conjugated mesomeric betaines (CMBs) [ 34 ]. Related work on other five-membered CMBs in equilibrium with their tautomeric NHCs was published by the groups of César and Lavigne [ 35 , 36 , 37 ], Braunstein and Danopoulos [ 38 , 39 , 40 ], Ganter [ 41 ] and Schmidt [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], who also provided the first review of this burgeoning field [ 50 ]. We demonstrated that the electronic properties of 2 ′ are very similar to those of the “Enders carbene” ( 1 ) [ 31 , 32 , 33 ], as is reflected by their essentially identical Tolman Electronic Parameter (TEP) values [ 51 ] as well as by the very similar 77 Se NMR chemical shift values (∆δ = 4 ppm) determined for their corresponding selenone derivatives.…”
Section: Introductionmentioning
confidence: 99%